Preclinical studies of an AAV8-CYP4V2 gene therapy VGR-R01 for the treatment of Bietti crystalline dystrophy - Wenjing Luo; Lu Guo; Liang Lu; Nan Huang; Yezheng Tao; Yufei Zhang; Yanrong Cao; Shin-Shay Tian; Xiaoping Zhao; Xi Zhu (Molecular Therapy: Methods & Clinical Development)
Bietti crystalline dystrophy (BCD) is an autosomal recessive disorder caused by loss-of-function mutations in the CYP4V2 gene, characterized by crystal-like lipid deposits in the retina, progressive photoreceptor loss, and retinal pigment epithelium (RPE) deterioration. Currently, there are no approved treatments for BCD. VGR-R01, an investigational gene therapy, uses subretinal administration of recombinant adeno-associated virus type 8 (AAV8) vector to deliver the human CYP4V2 gene. This therapy is now undergoing phase 1/2 clinical trials (NCT05694598). The pre-clinical study results for VGR-R01 are summarized, with a focus on its pharmacology, pharmacokinetics, and toxicology. The in vitro cellular studies demonstrated that VGR-R01 induces a dose-dependent expression of the CYP4V2 protein, which significantly enhances fatty acid hydroxylase activity and reduces lipid droplet accumulations in the RPE cells. In vivo, VGR-R01 showed effectiveness in improving electroretinogram (ERG) amplitudes in 8-month-old Cyp4v3−/− mice. VGR-R01 was well tolerated in New Zealand rabbits and non-human primates (NHPs). Furthermore, after subretinal administration, VGR-R01 was primarily distributed in the ocular tissues, especially in the retina, with minimal systemic presence, notably in the gonads. Overall, these results support the potential for clinical application of VGR-R01 in treating BCD.